Novel end-to-side one-layer continuous pancreaticojejunostomy vs. end-to-end invaginated pancreaticojejunostomy in pancreatoduodenectomy: A single-center retrospective study - Luo, Dong; Li, Yixiong; Ji, Liandong; Gong, Xuejun (Frontiers in Surgery, 2023)
Background and Objective Postoperative pancreatic fistula (POPF) is the most common critical complication after pancreatoduodenectomy (PD) and is the primary reason for increased mortality and morbidity after PD. We aim to investigate the clinical significance of a novel approach, i.e., end-to-side one-layer continuous pancreaticojejunostomy, for patients with PD. Methods The clinical data of 65 patients who underwent pancreatoduodenectomy at the Xiangya Hospital, Central South University, from September 2020 to December 2021 were retrospectively analyzed. Results Forty patients underwent end-to-end invaginated pancreaticojejunostomy, and 25 underwent the novel end-to-side one-layer continuous pancreaticojejunostomy. No significant differences were observed in pancreatic fistula, intraperitoneal infection, intraperitoneal bleeding, reoperation, postoperative hospital stay, or perioperative death between the two groups. However, the novel end-to-side one-layer continuous pancreaticojejunostomy group had significantly shorter operation duration (32.6 ± 5.1 min vs. 8.3 ± 2.2 min, p < 0.001). The incidence of pancreatic fistula in the novel pancreaticojejunostomy group was 12%, including two cases of grade A POPF and only one case of grade B POPF. No cases of grade C POPF occurred. No deaths were observed during the perioperative period. Conclusions The novel anastomosis method leads to a shorter operation duration than the traditional anastomosis method and does not increase postoperative complications. In conclusion, it is a simplified and feasible method for pancreatic anastomosis.